Intensive care nurses’ knowledge and attitudes towards catheter-related bloodstream infections and evidence-based nursing: results from a descriptive and cross-sectional survey conducted in a hospital in Türkiye - Elif Gezginci Akpinar; Habibe Filiz Akdemir; Sonay Goktas (BMC Nursing)
Abstract Background Intensive care units pose a risk for catheter-related infections because they are the setting of frequent catheter use. This study aimed to determine intensive care nurses’ knowledge and attitudes towards preventing catheter-related bloodstream infections and their attitudes towards evidence-based practices. Methods This descriptive and cross-sectional survey was conducted between June and October 2021 among 148 nurses working in the adult intensive care units of a hospital in Istanbul. Data were collected using a descriptive characteristics form, the Peripheral and Central Venous Catheter-Related Bloodstream Infection Prevention Knowledge and Attitude Scale, and the Attitude Towards Evidence-Based Nursing. Data were analysed with Pearson correlation test, linear regression analysis, t-test and ANOVA test. Results A significant (148/162) portion of the intensive care nurses participated in the survey, with a response rate of 91%. Among the participants, 83.8% had received training on preventing catheter-related bloodstream infections. The nurses had good knowledge and attitudes towards preventing catheter-related bloodstream infections (62.80 ± 4.78) and moderate attitudes towards evidence-based nursing (48.30 ± 4.40). A weak positive correlation was found between knowledge and attitude towards preventing catheter-related infections total score and attitudes towards evidence-based nursing total score (r = 0.334, p < 0.001). The change in total knowledge and attitudes towards preventing catheter-related infections score explained 10.6% of the variation in total attitude towards evidence-based nursing score (R2 = 0.106). Conclusion The increase in nurses’ knowledge and attitudes towards preventing catheter-related bloodstream infections was associated with better attitudes towards evidence-based nursing. It is recommended that continuing education be provided to nurses on evidence-based practices, including catheter-related infection precautions. Clinical trial number Not applicable.